Effect of Shoot Bending and Fruit Thinning on Productivity of Guava (Journal of Environmental Science and Natural Resources, 2013)
The study was carried out at the Germplasm Centre of Fruit Tree Improvement Programme (GPC-FTIP), Bangladesh Agricultural University, Mymensingh during the period February, 2011 to March, 2012 to find out the effect of shoot bending and fruit thinning on productivity of guava. The treatments of the experiment were four varieties of guava viz., Swarupkathi, BAU piyara-5, Chiang Mai (round) and Chiang Mai (long) and six different management practices viz., (i) control (no shoot bending + no fruit thinning); (ii) shoot bending; (iii) 25% fruit thinning; (iv) 50% fruit thinning; (v) 75% fruit thinning and (vi) 100% fruit thinning. The ages of the plants were 4-5 years. Results revealed that the variety Chiang Mai (round) showed superiority over BAU piyara-5, Chiang Mai (long) and Swarupkathi in respect of fruit yield (15.63 kg/plant) and fruit retention (72.92%) during on-season but during off-season, Swarupkathi showed superiority over Chiang Mai (round), BAU piyara-5 and Chiang Mai (long) in case of number of flowers set per plant (127.44), number of fruits set per plant (75.28), fruit retention (88.66%) and yield (11.78 kg/plant). Different management practices had significant effect on all studied parameters in both seasons. Fifty percent fruit thinning treatment showed the highest fruit yield (20.46 kg/plant) and 75% fruit thinning treatment performed lowest fruit yield (10.06 kg/plant) during on-season but during off-season shoot bending performed highest fruit yield (13.50 kg/plant). Highest fruit retention in both seasons (on-season 89.28% and off-season 90.47%) was observed in 50% fruit thinning treatment. In case of combined effect of variety and different management practices, 50% fruit thinning treatment combined with Chiang Mai (round) produced highest yield (23.15 kg/plant) and fruit retention (92.72%) during on-season, but shoot bending treatment combined with Swarupkathi gave the highest yield (16.06 kg/plant) and 50% fruit thinning combined with Swarupkathi showed highest fruit retention (94.12%) during off-season.DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14808 J. Environ. Sci. & Natural Resources, 5(2): 167-172 2012